SplitT-Pong as an easy tool to select talents for table tennis - Szily, M.; Valovics, G. (Proceedings Book of The 16th ITTF Sports Science Congress Budapest (HUN), April 19th - 20th, 2019, 2020)
To find and select table tennis talents is not an easy job. First of all, organize an event either at your club or in schools. The appropriate advertising and needed equipment are very important. SplitT-Pong is an afloat table with measurements of 200cm X 120cm. With SplitT-Pong you can play ping-pong in the water. You can easily move the table and transport it by car. Getting started with SplitTPong is equally easy: you put the table into the water, start to play and many children will want to join you. The rackets of SplitT-Pong are glove-paddles which give you a feeling of playing with your palm. The diameter of the SplitT-Pong`s ball is about 5 cm, and it is made from rubber or sponge. The shape of the paddles and the ball makes it possible to learn SplitT-Pong in no time. The real talents can play after 2-3 minutes and enjoy the game. The rules are much simpler than in table tennis. You play outside and not in the hall, with large balls allowing you to play in the wind (up until 5 m/s). Another advantage of SplitT-Pong, that you can adjust the high of the table in the water. Despite the differences between SplitT-Pong and table tennis, the same qualities are needed for both types of entertainment. We make recruitment for table tennis mainly in the summer and in the leisure time of children. This is much more effective than the conventional recruitment.